Making the case for Africa and the democratic republic of the Congo as the global rare earth element supply leaders - Gibson, Pandwe Aletha (Frontiers in Environmental Science, 2023)
The initiative to electrify and decarbonize economies over the next two decades, particularly in the energy and transportation sectors, is going to cause a significant increase in demand for critical rare earth elements (REEs). Rare earth elements have already proved themselves highly useful, contributing to many everyday items including batteries, electric vehicles (EV), computer components, photovoltaic panels, and turbines to name a few examples. The number of countries outside of the United States (US) that currently source and provide these critical elements is limited, posing implications for the security and continuity of the global and national supply chain and specifically to the national security of the US. This article is a mini review of the existing literature with recommendations for partnerships. It discusses potential stress points in the current supply chain of REEs and explores the feasibility of expanded American partnerships with Africa and the Democratic Republic of the Congo (DRC) specifically to address opportunities to strengthen the security and transparency of the global supply chain of REEs. In Africa, REEs are concentrated in countries like South Africa, Madagascar, Malawi, Kenya, Namibia, the DRC, Mozambique, Tanzania, Zambia, and Burundi. These countries have significant quantities of neodymium, praseodymium, and dysprosium among other REEs that are required in the numerous technological items (including green technologies) that are manufactured today (IEA 2022). The framework for extracting the elements from those countries requires specific attention to ensure the preservation of natural assets that are key to global health.